2015
DOI: 10.1089/jwh.2014.4879
|View full text |Cite|
|
Sign up to set email alerts
|

Intimate Partner Violence and Its Health Impact on Ethnic Minority Women

Abstract: In the United States, intimate partner violence (IPV) against women disproportionately affects ethnic minorities. Further, disparities related to socioeconomic and foreign-born status impact the adverse physical and mental health outcomes as a result of IPV, further exacerbating these health consequences. This article reviews 36 U.S. studies on the physical (e.g., multiple injuries, disordered eating patterns), mental (e.g., depression, post-traumatic stress disorder), and sexual and reproductive health condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
199
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(225 citation statements)
references
References 74 publications
(78 reference statements)
3
199
1
2
Order By: Relevance
“…American research has shown that the rate of IPV and the associated health effects vary for different groups of ethnic minorities [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…American research has shown that the rate of IPV and the associated health effects vary for different groups of ethnic minorities [16].…”
Section: Discussionmentioning
confidence: 99%
“…If the impact of abuse on mental health varies for natives and non-natives this should have implications for care. 4 Few studies, and none European, have investigated the role of immigrant status or ethnicity in the relationship between a history of abuse and mental health among pregnant women [15,16]. A Canadian cross-sectional study of around five thousand pregnant women concludes that immigrant status does not change the association between violence and depression [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly one in three (35.6%) women in the U.S. have experienced rape, physical violence, or stalking by a partner at some point in their lives (Breiding, Chen, and Black 2014). In addition to serious injuries, IPV can have serious mental health consequences, including suicide attempts, and has been associated with premature deaths (Gold et al 2012;Stockman, Hayashi, and Campbell 2015). Risk factors associated with IPV victimization include socio-demographic factors; health behaviors, such as heavy alcohol or drug use; mental health conditions; and history of being in abusive relationships (Brownridge et al 2011;Chu, Goodwin, and D'Angelo 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although abuse and violence affects all communities, it disproportionately takes a toll on vulnerable populations such as indigenous communities, undocumented immigrants and other minority and marginalised groups because of its interaction with other economic, social and health inequities (Nixon & Humphreys, 2010;Stockman, Hayashi, & Campbell, 2015). Given that family abuse and violence is a complex problem enmeshed in societal values, beliefs and responses, decreasing if not eliminating its presence, increasing safety and decreasing harms cannot occur through simple solutions.…”
mentioning
confidence: 99%